Les retraites de rédaction structurées auprès des doctorant[e]s : Quelles conditions favorisent une expérience de rédaction légitime, productive et plaisante? - Tremblay Wragg, Émilie; Vincent, Cynthia; Lison, Christelle; Gilbert, William; Valois, Philippe; Mathieu-Chartier, Sara (Canadian Journal of Education/Revue canadienne de l’éducation, 2021)
Thesis writing is challenging for many PhD candidates. To support them, structured writing retreats represent a strategy for consideration, although little has been documented on the topic. This article presents results from a mixed-method study (N = 210) combining questionnaires and interviews, aiming to understand the effects of Thesez-vous writing retreats to 1) document benefits of writing retreats, namely encouraging writing, legitimizing writing and ensuring a fulfilling experience, and to 2) identify conditions maximizing these benefits. More broadly, this article conveys the possibility to rethink and reframe thesis writing to create a productive, collective and pleasant experience. Keywords: thesis editing, writing retreats, benefits, flow, scientific productivity